Magnetic hydrogel, surface modified Ti implant with anisotropic magnetic hydrogel coating and application of surface modified Ti implant
By preparing anisotropic magnetic hydrogel coating on titanium implants and combining dynamic magnetic fields, the problem of difficulty in simulating the mechanical environment of BMSCs in the prior art is solved, and the anisotropic morphology and machinery on titanium implants are realized The combination of stimulation provides a platform to simulate the bone physical microenvironment to study its impact on BMSCs.
Patent Information
- Application Number
- CN202411564433.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The prior art is difficult to effectively simulate the mechanical environment of bone marrow mesenchymal stem cells (BMSCs), affecting their adhesion, migration and differentiation.
The organic combination of anisotropic morphology and mechanical stimulation on the titanium implant is achieved by preparing anisotropic magnetic hydrogel coating on the titanium implant and combining a dynamic magnetic field.
The organic combination of anisotropic morphology and mechanical stimulation on Ti implants is achieved, providing a platform to simulate the physical microenvironment of bone, and studying its impact on BMSCs adhesion, osteogenic differentiation and osteointegration.
Smart Images

Figure CN119424731A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of bioengineering, and in particular to a magnetic hydrogel, a surface-modified Ti implant with an anisotropic magnetic hydrogel coating, and applications thereof. Background Art
[0002] Pure titanium and its alloys are widely used in oral implants, orthopedics, total joint repair and other fields due to their excellent biocompatibility, mechanical strength, chemical stability, durability and corrosion resistance. However, there are still many defects in its surface properties, which affects its long-term application. Previous studies have shown that bone marrow mesenchymal stem cells (BMSCs) and their lineage differentiated progeny (such as osteoblasts) and osteocytes are mechanically sensitive in bones, and the extracellular mechanical microenvironment has a significant effect on the adhesion, migration and differentiation of BMSCs. Different mechanical stimuli can activate different signaling molecules and pathways to guide the differentiation of BMSCs. Mechanical stimulation of appropriate intensity can convert the differentiation direction of BMSCs from adipogenic differentiation to osteogenic differentiation, but the simulation technology of the mechanical environment of BMSCs still needs to be developed.
[0003] Researchers at home and abroad have invented various surface modification technologies and methods. From the perspective of cell microenvironment, traditional modification strategies are mainly divided into two categories: physical microenvironment and biochemical microenvironment. The strategies for regulating the physical microenvironment mainly include increasing the surface roughness of titanium materials, introducing porous structures and anisotropic bionic structures, etc., while the strategies for regulating the biochemical microenvironment include fixing bioactive molecules and constructing inorganic or organic coatings. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a magnetic hydrogel, a surface-modified Ti implant with an anisotropic magnetic hydrogel coating and its application in view of the deficiencies in the above-mentioned prior art. The present invention deposits Fe3O4 nanoparticles on carboxylated cellulose nanofibers (CNF) by a coprecipitation method, and prepares magnetic cellulose nanoparticles (PMNP) by modifying the surface thereof with polydopamine, and then incorporates the nanoparticles and calcium phosphate oligomers (CPO) into a GelMA hydrogel solution (GelMA / CPO / PMNP), and then applies the solution to a polydopamine-modified Ti implant (Ti-PDA), and after forming an anisotropic structure in a magnetic field, photocrosslinking is performed to obtain a Ti implant with an anisotropic hydrogel coating (Ti-GC-aPMNP). The present invention prepares an anisotropic magnetic hydrogel coating on Ti implants and combines it with a dynamic magnetic field to achieve an organic combination of anisotropic morphology and mechanical stimulation on Ti implants. Based on this, an in vitro cell culture platform can be constructed to study the effects of anisotropic morphology and dynamic mechanical stimulation on Ti implants on BMSCs adhesion, osteogenic differentiation and final bone integration.
[0005] To achieve the above object, the technical solution adopted by the present invention is: In a first aspect of the present invention, a magnetic hydrogel is provided, which is prepared by the following steps:
[0006] S1. Preparation of polydopamine-coated magnetic nanocellulose PMNP:
[0007] S1-1, dissolving carboxylated cellulose nanofibers in deionized water, and ultrasonicating to obtain a cellulose nanofiber solution;
[0008] S1-2, adding ferrous chloride tetrahydrate and ferric chloride hexahydrate, stirring, adding ammonia water dropwise while stirring, heating and stirring to react, separating with a magnet after the reaction is completed, washing the magnetic product, and obtaining magnetic nanocellulose MNP;
[0009] S1-3, dispersing MNP in Tris solution, then adding dopamine hydrochloride, mixing by ultrasonication, and shaking on a shaker in the dark to react, after the reaction, washing and freeze-drying the product to obtain PMNP;
[0010] S2, preparing methacrylylated gelatin GelMA;
[0011] S3. Preparation of calcium phosphate oligomer CPO:
[0012] Dissolve CaCl2·2H2O in ethanol, add triethylamine under stirring, and then dropwise add the alcohol solution of H3PO4. After the dropwise addition is completed, centrifuge and wash the solid product to obtain CPO;
[0013] S4. Preparation of precursor solution for magnetic hydrogel:
[0014] Under light-proof conditions, GelMA, CPO and photoinitiator were dissolved in PBS solution, and then PMNP was added and mixed evenly to obtain a precursor solution of magnetic hydrogel;
[0015] S5. Prepare magnetic hydrogel by any of the following methods:
[0016] a. coating the precursor solution of magnetic hydrogel and curing it with blue-violet light to obtain magnetic hydrogel with randomly distributed magnetic particles;
[0017] b. After coating, the precursor solution of magnetic hydrogel is subjected to magnetic orientation treatment in a magnetic field, and then cured with blue-violet light to obtain anisotropic magnetic hydrogel.
[0018] Preferably, step S1 specifically comprises:
[0019] S1-1, dissolving 200 mg of carboxylated cellulose nanofibers in 100 mL of deionized water, and ultrasonicating for 30 minutes to obtain a cellulose nanofiber solution;
[0020] S1-2, after blowing nitrogen gas into the cellulose nanofiber solution for 20 minutes, 180 mg of ferrous chloride tetrahydrate and 470 mg of ferric chloride hexahydrate were added, and the mixture was stirred for 30 minutes. Ammonia water was added dropwise under stirring to adjust the pH to 10, and the mixture was stirred at 70°C for 30 minutes. 100 mL of deionized water was added to terminate the reaction, and then the mixture was separated by a magnet. The magnetic product was washed with anhydrous ethanol and deionized water in sequence to obtain magnetic nanocellulose MNP;
[0021] S1-3. Disperse 100 mg of MNPs in 50 mL of Tris solution, then add 50 mg of dopamine hydrochloride, mix by ultrasonication for 5 minutes, shake on a shaker at 50 rpm in the dark overnight, wash the product with deionized water and anhydrous ethanol, and lyophilize to obtain PMNPs.
[0022] Preferably, step S2 specifically comprises:
[0023] At 50°C, 5 g of type A gelatin was added to 50 ml of PBS and stirred until completely dissolved. 6 mL of methacrylic anhydride was added under light-shielded conditions. After reacting for 2 h, 200 mL of PBS preheated to 60°C was added to terminate the reaction. The reaction product was dialyzed in a dialysis bag with a molecular cutoff of 11K Da at 50°C for 4 days. The dialysate in the dialysis bag was taken and freeze-dried to obtain GelMA.
[0024] Preferably, step S3 specifically comprises:
[0025] 2.94 g of CaCl2·2H2O was dissolved in 0.4 L of ethanol, and 55.45 mL of triethylamine was added under magnetic stirring. Then, an alcohol solution of H3PO4 was added dropwise under magnetic stirring at room temperature. The mixture was reacted for 12 h, centrifuged, and the solid product was washed to obtain CPO.
[0026] The alcohol solution of H3PO4 is obtained by dissolving 1.045 mL of H3PO4 in 20.00 mL of ethanol.
[0027] Preferably, step S4 is specifically:
[0028] S4-1. Dissolve GelMA, CPO and photoinitiator LAP in PBS solution at 60°C in the dark, so that the mass volume concentrations of GelMA, CPO and photoinitiator LAP are 15%, 2% and 0.2% respectively;
[0029] S4-2, adding PMNP and mixing evenly to make the mass volume concentration of PMNP be 0.38-6%, and obtaining a precursor solution of magnetic hydrogel.
[0030] Preferably, step S5 is specifically:
[0031] The magnetic hydrogel is prepared by any of the following methods:
[0032] a. After coating, the precursor solution of magnetic hydrogel is irradiated with blue-violet light for 30-90 seconds to solidify, thereby obtaining a magnetic hydrogel with randomly distributed magnetic particles;
[0033] b. After coating, the precursor solution of the magnetic hydrogel is subjected to magnetic orientation treatment in a uniform magnetic field of 60-100 mT for 2-10 seconds and then cured by irradiation with blue-violet light for 30-90 seconds to obtain anisotropic magnetic hydrogel.
[0034] In a second aspect of the present invention, a surface-modified titanium material having an anisotropic magnetic hydrogel coating is provided, which comprises a titanium material body and a magnetic hydrogel coating arranged on the surface of the titanium material body. The preparation method of the magnetic hydrogel coating is: coating the precursor liquid of the magnetic hydrogel as described above on the surface of the titanium material body, then performing magnetic orientation treatment in a magnetic field, and curing with blue-violet light to form the magnetic hydrogel coating.
[0035] Preferably, the surface-modified titanium material having anisotropic magnetic hydrogel coating is prepared by the following method:
[0036] 1) Polydopamine modification of titanium body:
[0037] After washing the titanium body, immersing it in an alkaline solution under heating, drying it, and immersing it in a Tris solution, adding dopamine hydrochloride to the Tris solution, reacting on a shaker in the dark, washing and drying the product, and obtaining a polydopamine-modified titanium body;
[0038] 2) The precursor solution of the magnetic hydrogel as described above is dropped onto the surface of the titanium material modified with polydopamine, coated evenly, and then subjected to magnetic orientation treatment in a magnetic field, and blue-violet light is cured to form the magnetic hydrogel coating, thereby obtaining a surface-modified titanium material having an anisotropic magnetic hydrogel coating.
[0039] Preferably, the surface-modified titanium material having anisotropic magnetic hydrogel coating is prepared by the following method:
[0040] 1) Polydopamine modification of titanium body:
[0041] The titanium body was washed with acetone, anhydrous ethanol and deionized water, then immersed in a 5M NaOH solution at 60°C for 24 hours, dried at 60°C and immersed in a 10mM Tris solution with a pH of 8.5, dopamine hydrochloride was added to the Tris solution to make the concentration of dopamine hydrochloride 1 mg / mL, incubated on a shaker in the dark overnight, the product was washed with deionized water, and dried to obtain a polydopamine-modified titanium body;
[0042] 2) The precursor solution of the magnetic hydrogel as described above is dropped onto the surface of the titanium material modified with polydopamine, and the coating is evenly applied, and then the magnetic orientation treatment is carried out in a uniform magnetic field of 60-100 mT for 2-10 seconds, and the magnetic hydrogel coating is solidified by irradiating with blue-violet light for 30-90 seconds to form the magnetic hydrogel coating, thereby obtaining a surface-modified titanium material having an anisotropic magnetic hydrogel coating.
[0043] The third aspect of the present invention provides an application of a surface-modified titanium material with an anisotropic magnetic hydrogel coating as described above, which is used as a Ti implant to simulate the physical microenvironment of bone and to construct an in vitro cell culture platform for studying the effects of mechanical stimulation on the adhesion and osteogenic differentiation of BMSCs.
[0044] The beneficial effects of the present invention are:
[0045] The present invention uniformly deposits Fe3O4 nanoparticles on carboxylated cellulose nanofibers and modifies them with polydopamine to prepare magnetic cellulose nanoparticles with high biocompatibility and superparamagnetism. The particles can sensitively respond to weak magnetic fields (no more than 20mT); the particles are incorporated into a GelMA hydrogel solution together with calcium phosphate oligomers, and then the solution is coated on a polydopamine-modified Ti material, and after an anisotropic structure is formed in a magnetic field, photocrosslinking is performed to finally obtain a surface-modified Ti implant with an anisotropic magnetic hydrogel coating. The magnetic hydrogel coating has anisotropic structure and mechanical properties, and can simulate the anisotropy of bone to a certain extent;
[0046] The present invention prepares an anisotropic magnetic hydrogel coating on a Ti implant and combines it with a dynamic magnetic field to achieve an organic combination of anisotropic morphology and mechanical stimulation on the Ti implant. Based on the magnetic hydrogel coating, the present invention can construct an extracellular cell culture platform for studying the effects of anisotropic morphology and dynamic mechanical stimulation on BMSCs adhesion and osteogenic differentiation. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 The system preparation process of the present invention is as follows: (A) the preparation process of the titanium material body modified with polydopamine; (B) the preparation process of the magnetic cellulose modified with dopamine; (C) the preparation process of the titanium-based anisotropic magnetic hydrogel (i.e., the surface-modified titanium material with anisotropic magnetic hydrogel coating);
[0048] Figure 2 The performance test results of each hydrogel in Example 1 of the present invention are as follows: (A) microstructure of hydrogel; (B) magnetic response performance; (C) compression test of hydrogel; (D) XRD spectra of nanoparticles such as MNP and PDA-coated MNP (PMNP); (E) VSM diagram of magnetic nanoparticles; (F) FT-IR spectrum analysis diagram; (G) thermogravimetric analysis;
[0049] Figure 3 The test results of the effects of the magnetic hydrogel and related materials of the system of the present invention on cell compatibility: (A) Relative cell viability of hydrogels doped with different concentrations of CPO (1%, 2%, 3%) and PMNP particles (0.75%, 1.5%, 3%, 6%); (B) Cell proliferation effect diagram; (C) Fluorescence image of FDA / PI staining (green - live cells, red - dead cells), scale 500μm.
[0050] Figure 4 The test results of the effects of the magnetic hydrogel and related materials of the system of the present invention on cell morphology: (A) Fluorescence image of cytoskeleton and nucleus staining after 4 days of culture (green-cytoskeleton, blue-nucleus); (B) Fluorescence image of the arrangement direction of magnetic particles in the anisotropic hydrogel coating and the arrangement direction of cells; (C) Box plot of cell spreading area; (D) Cell aspect ratio diagram; (E) Statistical diagram of the angle θ between the long axis direction of the cell and the horizontal line (n=10).
[0051] Figure 5 The test results of the system of the present invention based on dynamic magnetic stimulation and anisotropic magnetic hydrogel on cell osteogenic differentiation: (A, C) alkaline phosphatase staining and activity analysis of cells in Ti-PDA, Ti-G, Ti-GC, Ti-G-rPMNP, Ti-GC-rPMNP, Ti-GC-aPMNP and Ti-GC-aPMNP for 4 and 7 days; (B, D) collagen staining and quantitative analysis for 14 days; (E) mineralization staining and quantitative analysis for 14 days. All data are shown as mean ± SD, n = 3, *p < 0.05, **p < 0.01 and ***p < 0.001. DETAILED DESCRIPTION
[0052] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0053] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0054] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0055] Example 1
[0056] A magnetic hydrogel and a surface-modified titanium material having an anisotropic magnetic hydrogel coating based thereon. The magnetic hydrogel is prepared by the following steps:
[0057] S1. Preparation of polydopamine-coated magnetic nanocellulose PMNP:
[0058] S1-1, dissolving 200 mg of carboxylated cellulose nanofibers in 100 mL of deionized water, and ultrasonicating for 30 minutes to obtain a 0.2 wt% cellulose nanofiber solution after full dissolution;
[0059] S1-2, after blowing nitrogen gas into the cellulose nanofiber solution for 20 minutes, 180 mg of ferrous chloride tetrahydrate and 470 mg of ferric chloride hexahydrate were added, and the mixture was stirred vigorously for 30 minutes. Ammonia water was added dropwise under vigorous stirring to adjust the pH to 10, and the mixture was stirred at 70°C for 30 minutes. 100 mL of deionized water was added to terminate the reaction, and then the mixture was separated by a magnet. The magnetic product was washed three times with anhydrous ethanol and deionized water in sequence to obtain magnetic nanocellulose MNP;
[0060] S1-3. Disperse 100 mg of MNPs in 50 mL of Tris solution, then add 50 mg of dopamine hydrochloride, mix by ultrasonication for 5 minutes, shake on a shaker at 50 rpm overnight in the dark, wash the product three times with deionized water and anhydrous ethanol, and lyophilize to obtain PMNPs.
[0061] S2. Preparation of methacrylated gelatin GelMA:
[0062] At 50°C, 5 g of type A gelatin (purchased from Aladdin, brand number 9000-70-8) was added to 50 ml of PBS and stirred until completely dissolved. 6 mL of methacrylic anhydride (MA) was added under light-shielded conditions. After reacting for 2 h, 200 mL of PBS preheated to 60°C was added to terminate the reaction. The reaction product was dialyzed at 50°C in a dialysis bag with a molecular cutoff of 11K Da for 4 days. The dialysate in the dialysis bag was taken and freeze-dried to obtain GelMA.
[0063] S3. Preparation of calcium phosphate oligomer CPO:
[0064] 2.94 g of CaCl2·2H2O was dissolved in 0.4 L of ethanol, and 55.45 mL of triethylamine was added under magnetic stirring. Then, an alcohol solution of H3PO4 was added dropwise under magnetic stirring at room temperature. The mixture was reacted for 12 h, and centrifuged at 6000 rpm. The solid product was washed three times with ethanol to remove the residual triethylamine, thereby obtaining CPO. The solid product was resuspended in deionized water to form a uniform emulsion with a concentration of about 3 mg / mL.
[0065] The alcohol solution of H3PO4 is obtained by dissolving 1.045 mL of H3PO4 in 20.00 mL of ethanol.
[0066] S4. Preparation of precursor solution for magnetic hydrogel:
[0067] S4-1. At 60°C in the dark, a uniform emulsion of GelMA and CPO and a photoinitiator LAP (lithium phenyl (2,4,6-trimethylbenzoyl) phosphate) were dissolved in a PBS solution to make the mass volume concentrations of GelMA, CPO and photoinitiator LAP 15% (w / v), 2% (w / v) and 0.2% (w / v), respectively.
[0068] S4-2. Add a certain amount of PMNP and mix well to make the mass volume concentration of PMNP be 0, 0.38, 0.75, 1.5, 3, 6% (w / v), respectively, to obtain precursor solutions of magnetic hydrogels with different PMNP contents.
[0069] S5. Prepare magnetic hydrogel by any of the following methods:
[0070] a. After coating, the precursor solution of magnetic hydrogel is irradiated with blue-violet light for 60 seconds to solidify, thereby obtaining a magnetic hydrogel with randomly distributed magnetic particles;
[0071] b. After coating, the precursor solution of magnetic hydrogel is subjected to magnetic orientation treatment in a uniform magnetic field of 80 mT for 5 seconds and then cured by irradiation with blue-violet light for 60 seconds to obtain anisotropic magnetic hydrogel.
[0072] The preparation of magnetic hydrogel will be further described below in conjunction with a specific titanium material body.
[0073] This embodiment also provides a surface-modified titanium material having an anisotropic magnetic hydrogel coating, which is prepared by the following method:
[0074] 1) Polydopamine modification of titanium body:
[0075] The titanium body (10 mm x 10 mm titanium foil) was washed three times with acetone, anhydrous ethanol and deionized water respectively, then immersed in a 5 M NaOH solution at 60°C for 24 h, dried at 60°C and immersed in a 10 mM Tris solution (the pH was adjusted to 8.5 with HCl), dopamine hydrochloride was added to the Tris solution to make the concentration of dopamine hydrochloride 1 mg / mL, and incubated on a shaker in the dark overnight. The product was washed with deionized water and dried to obtain a polydopamine-modified titanium body, which was recorded as Ti-PDA;
[0076] 2) 25 μL of the precursor solution of the magnetic hydrogel prepared in step S4 above is dropped onto the surface of the polydopamine-modified titanium material, evenly coated, and then magnetically oriented for 5 seconds in a uniform magnetic field of 80 mT, with the direction of the magnetic field parallel to the plane of the titanium foil. The magnetic hydrogel coating is cross-linked and cured by irradiation with blue-violet light for 60 seconds to form a magnetic hydrogel coating, thereby obtaining a surface-modified titanium material with an anisotropic magnetic hydrogel coating, i.e., oriented (Alined) magnetic particles, recorded as Ti-GC-aPMNP.
[0077] As a comparison, a surface-modified titanium material having a magnetic hydrogel coating with randomly distributed magnetic particles was prepared by the following method:
[0078] 25 μL of the precursor solution of the magnetic hydrogel prepared in step S4 above is dropped onto the surface of the polydopamine-modified titanium material, coated evenly, and irradiated with blue-violet light for 60 seconds for cross-linking and curing to form a magnetic hydrogel coating, thereby obtaining a surface-modified titanium material having a magnetic hydrogel coating with randomly distributed magnetic particles, that is, non-oriented (Random) magnetic particles, recorded as Ti-GC-rPMNP.
[0079] Furthermore, the same method as Ti-GC-rPMNP was used to prepare surface-modified titanium material with pure GelMA hydrogel coating: Ti-G (CPO and PMNP were not added in step S4), and surface-modified titanium material with hydrogel coating only doped with CPO: Ti-GC (PMNP was not added in step S4), which were used for subsequent detection and experiments, respectively.
[0080] Performance Characterization and Testing
[0081] 1. The successful synthesis of magnetic hydrogel was demonstrated by SEM, XRD and VSM. The results of FT-IR spectroscopy showed that nano-ferroferric oxide (Fe3O4) was successfully deposited on carboxylated cellulose nanofibers by coprecipitation. The thermal stability of the particles was determined by thermogravimetric analysis. The thermogravimetric experimental parameters were: temperature: room temperature to 700°C, heating rate: 10K / min, experimental atmosphere: nitrogen, gas flow rate: 100mL / min.
[0082] 2. The mechanical properties of the hydrogel were determined using a compression test method. Briefly, the hydrogel disc was placed on the Instalon 5567 platform and the compression test mode was used. The gel was compressed to 60% strain. The deformation rate was 1 mm / min. The shear stress of the gel was the corresponding stress change during the 60% strain process.
[0083] 3. Hydrophilicity test: The hydrophilicity of each group of hydrogels and ppyNWs was measured using water contact angle. The gel sheet and the ppyNWs solution coated on the glass slide were dried, placed on the stage, the camera was turned on, and the same volume of water droplets were dropped and photographed. The baseline and tangent line were drawn using software to measure the contact angle.
[0084] Test results:
[0085] The microstructure of the hydrogel was characterized by SEM. Figure 2 A). The results show that the pore size of pure 15% GelMA hydrogel is relatively uniform (~5μm), and the pore size decreases after adding particles. After magnetic orientation, an oriented structure appears inside the hydrogel, which shows that the method of constructing a hydrogel coating with anisotropic structure by magnetic orientation is effective.
[0086] PMNP particles in different concentration groups can respond quickly to the magnetic field and align in the direction of the magnetic field ( Figure 2 B), but in the 0.38% and 0.75% groups, the alignment of PMNP in the hydrogel was limited due to the low concentration, which was manifested in that the chain structures formed by PMNP were few and short. As for the 3.00% group, although there were obvious aligned chain structures, the width of these chain structures was not uniform, some were too thick, and others were too thin, indicating that these chain structures had a tendency to aggregate, which may affect the mechanical properties of the hydrogel coating. In contrast, the magnetic cellulose alignment effect of the 1.50% concentration group was the best, and the aligned chain structures were uniform.
[0087] Compression tests were performed on hydrogels containing magnetic particles of different concentrations (0, 0.38, 0.75, 1.5, 3.0% (w / v)) and orientations (Alined, A; Random, R). Figure 2 C).
[0088] Figure 2 In C, GelMA represents pure hydrogel coating, R-0.38 represents non-oriented hydrogel coating with PMNP concentration of 0.38% (w / v), R-0.75, R-1.5, and R-3 have similar meanings, except for different PMNP concentrations; A-0.38 represents oriented hydrogel coating with PMNP concentration of 0.38% (w / v), A-0.75, A-1.5, and A-3 have similar meanings, except for different PMNP concentrations; GelMA-2CPO refers to a hydrogel coating doped with CPO at a concentration of 2% (w / v), R-1.5-2CPO represents a non-oriented hydrogel coating with a PMNP concentration of 1.5 (w / v) and a CPO concentration of 2% (w / v), and A-1.5-2CPO represents an oriented hydrogel coating with a PMNP concentration of 1.5 (w / v) and a CPO concentration of 2% (w / v); Figure 3 The GelMA-2CPO-1.5PMNP in the right image in C represents a non-oriented hydrogel coating.
[0089] The compression is set to 60%. Figure 2 From the compressive stress-strain curve in C, it can be seen that the 15% (w / v) GelMA hydrogel has high brittleness. When the concentration of PMNP particles is low (0.38%), the hydrogel begins to break when the compressive strain reaches 45-55%, which is manifested as a sharp drop in compressive stress; when the PMNP particle concentration is high (3%), the fracture strain increases, but the problem of GelMA hydrogel being too brittle is still not solved. The compression modulus is obtained by calculating the slope of the linear fitting curve of the stress-strain curve at 10%-20%. The compression modulus of pure 15% (w / v) GelMA hydrogel is 8.7kPa. As the PMNP particle concentration increases from 0.38% to 3%, the compression modulus of the hydrogel increases, but it is very limited, only increasing by 34%; magnetically induced particle arrangement can also increase the compression modulus of the hydrogel in the arrangement direction. However, simply adding magnetic particles does not seem to solve the problem of low stiffness and brittleness of GelMA hydrogel.
[0090] Therefore, the present invention adds calcium phosphate oligomers (CPO) to the hydrogel to enhance the basic mechanical properties of the GelMA hydrogel. CPO is an ultra-small size (particle size is not greater than 1nm) calcium phosphate compound, which can self-assemble into rod-shaped hydroxyapatite in the hydrogel, achieve strong protein (organic)-mineral (inorganic) interaction, improve the mechanical properties of the hydrogel, and overcome the high brittleness of the hydrogel. To this end, 2% CPO was added to the pure GelMA hydrogel and the magnetic hydrogel doped with 1.5% PMNP. The stress-strain curves are shown in Figure 2. Figure 2 As shown in the curves of GelMA-2CPO, R-1.5-2CPO and A-1.5-2CPO in C, adding 2% CPO nanoparticles can significantly improve the mechanical properties of GelMA hydrogel. When the compressive strain reaches 60%, the CPO-containing hydrogel still shows no signs of cracking. After the stress is removed, it can almost return to its original state, showing good toughness. Figure 2 From the compression modulus of the hydrogel in Figure C, it can be seen that after adding 2% (w / v) CPO to GelMA, the compression modulus of the GelMA hydrogel is significantly improved from the original 10-15 kPa to 30-35 kPa. Therefore, adding CPO to GelMA is expected to improve the inherent poor mechanical properties and brittleness of GelMA.
[0091] This example detects the XRD spectra (5°<2θ<85°) of nanoparticles such as cellulose nanofibers (CNF), Fe3O4, magnetic nanocellulose (MNP), and PDA-coated MNP (PMNP). The results show that ( Figure 2 D), Fe3O4, MNP, PMNP all have characteristic peaks at 30°, 35.4°, 43°, 56.9° and 62.5°, corresponding to the crystal planes (220), (311), (400), (511), (440), respectively, which are consistent with the main characteristic peaks of the Fe3O4 standard card, indicating that the main crystal structure of the above three particles is ferrosoferric oxide.
[0092] The magnetic hysteresis loops of the particles were measured by vibrating sample magnetometer (VSM). Figure 2 E), hysteresis loops of MNP and PMNP at 300 K. It can be seen that the coercivity of both particles is negligible and there is no obvious hysteresis loop, indicating that the particles have superparamagnetism. Both MNP and PMNP have relatively high saturation magnetization (Ms), which are 54.4emu / g and 42.7emu / g, respectively.
[0093] The results of FT-IR spectrum analysis showed that ( Figure 2 F), 3335cm -1 、3000cm -1 、1420cm -1 、1032cm -1 and 1653cm -1 The peaks at 1600 cm-1 correspond to OH stretching, NH stretching, CN stretching, C-OH stretching, and CC stretching, respectively. -1 、1407cm -1 There are two characteristic peaks of carboxyl groups in carboxylates, 543 cm -1 Corresponding to the Fe-O vibration peak of Fe3O4. 1600cm on CNF -1 、1407cm -1 The two strong absorption peaks indicate that CNF contains a large number of carboxyl groups, which explains why CNF can make the Fe3O4 size distribution uniform: a large number of uniformly distributed negatively charged carboxyl groups can attract positively charged iron ions, which greatly increases the nucleation sites of Fe3O4. The weakened carboxyl peak on MNP indicates that the carboxyl groups on CNF are largely consumed. After MNP is coated with polydopamine, 1032cm -1 The weakened C-OH stretching at 580 cm-1 is re-enhanced, which can be attributed to the large number of phenolic hydroxyl groups on polydopamine. -1 Down to 543cm -1 , which indicates that a strong interaction is formed between Fe3O4 and cellulose.
[0094] By thermogravimetric analysis ( Figure 2 G), the results show that the decomposition temperature of CNF is around 300 °C, the Fe3O4 content in MNP is about 77.46%, and the Fe3O4 content in PMNP is about 44.33%.
[0095] Example 2 Determination of the Cell Compatibility of the Surface Modified Titanium Material in Example 1
[0096] 1.CCK-8-Assay:
[0097] 1) placing the surface-modified titanium material prepared in Example 1 at the bottom of a 24-well plate;
[0098] 2) Then the third-generation BMSCs were seeded at a density of 4×104 / well on Ti substrates in different 24-well plates and the culture medium was changed once a day;
[0099] 3) After culturing for 1 day and 3 days, 400 μL of serum-free culture medium containing 10% CCK-8 solution was added to each well in a medium replacement manner and incubated at 37° C. for 1 hour.
[0100] 4) Take an appropriate amount of culture medium and measure the absorbance at 450 nm.
[0101] 2.FDA / PI live-dead staining:
[0102] 1) The third generation BMSCs were seeded at a density of 4×104 / well on different Ti-based materials in 24-well plates;
[0103] 2) After 4 days, discard the culture medium and wash twice with PBS, 5 minutes each time;
[0104] 3) Dilute the FDA / PI stock solution 500 times with serum-free medium to prepare the staining working solution;
[0105] 4) Add 1 mL of staining solution to each well and incubate for 15 minutes;
[0106] 5) Discard the staining solution, wash twice with PBS, 5 minutes each time, and observe and photograph under a fluorescence microscope.
[0107] The results of the test are as follows Figure 3 As shown:
[0108] Figure 3In A, GelMA represents a pure hydrogel coating, CPO1, CPO2, and CPO3 represent hydrogel coatings in which only 1%, 2%, and 3% (w / v) CPO are added in step S4 of Example 1, respectively, and PMNP0.75, PMNP1.5, PMNP3, and PMNP6 represent hydrogel coatings in which only 0.75%, 1.5%, 3%, and 6% (w / v) PMNP are added in step S4 of Example 1, respectively;
[0109] Figure 3 In B, Ti-PDA represents the titanium material modified with polydopamine, Ti-G represents the surface-modified titanium material with pure GelMA hydrogel coating, and Ti-GC represents the surface-modified titanium material with hydrogel coating only doped with CPO. (Ti-GC-PMNP is Ti-GC-rPMNP)
[0110] Figure 3 The results showed that 2% CPO was beneficial to the proliferation of MSCs and had the best cell proliferation ability and biocompatibility. Therefore, the CPO concentration was selected as 2% in subsequent experiments. For PMNP particles, when its concentration was low (0.75%, 1.5%), its cell proliferation ability was equivalent to that of the GelMA control group, indicating that lower concentrations of PMNP have good biocompatibility. In general, the prepared magnetic hydrogel coating Ti-GC-PMNP has no obvious cell proliferation toxicity ( Figure 3 B). FDA / PI( Figure 3 C) Live-dead staining experiments showed that in each group, living cells accounted for the vast majority, with almost no dead cells, and the cells had a high survival rate, indicating that the material had good biocompatibility and no obvious cytotoxicity.
[0111] Therefore, the CPO concentration was selected as 2% and the PMNP concentration was set as 1.5% for subsequent experiments.
[0112] Example 3 Detection of the effect of the surface modified titanium material of Example 1 on cell morphology changes
[0113] 1) BMSCs were inoculated on the surface-modified titanium material prepared in Example 1 and cultured for 4 days, then the culture medium was discarded and washed with PBS twice, each time for 5 minutes;
[0114] 2) Fix with 4% paraformaldehyde for 30 minutes and wash twice with PBS;
[0115] 3) The cell membrane was perforated with 0.2% Triton X-100 for 2 minutes and then washed twice with PBS;
[0116] 4) Add rhodamine-phalloidin and incubate overnight at 4°C in the dark for cytoskeleton staining;
[0117] 5) The next day, the dye solution was recovered and washed three times with PBS, each time for 5 minutes;
[0118] 6) Add DAPI to stain the cell nucleus for 30 minutes, recover the dye solution, and wash with PBS three times, 5 minutes each time;
[0119] 7) Seal the slides with 200 μL glycerol, store at 4°C, and observe and photograph under a fluorescence confocal microscope;
[0120] 8) ImageJ software was used to perform statistical analysis on cell area, ratio of major axis to minor axis and major axis angle.
[0121] Results: MSCs in each group were in a spreading state ( Figure 4 A), with more filamentous pseudopodia extending all around. Compared with the control group Ti-PDA (polydopamine-modified titanium body, without hydrogel layer), the box of the GelMA hydrogel coating modified group is generally higher ( Figure 4 C), i.e., a higher spreading area. The anisotropy of the hydrogel coating also has a significant effect on the spreading of cells. The anisotropic group (Ti-GC-aPMNP, Ti-GC-aPMNP+DMF) has a higher cell spreading area. (Ti-GC-aPMNP+DMF represents anisotropic hydrogel with an applied magnetic field)
[0122] Effects of anisotropy and dynamic mechanical stimulation on MSCs polarization (including cell aspect ratio and cell orientation):
[0123] Cell Aspect Ratio: Cell aspect ratio display ( Figure 4 D), the cells in the Ti-PDA and Ti-G groups had the lowest aspect ratios, mainly concentrated around 1.6; in contrast, the Ti-GC group had a higher cell aspect ratio, mainly distributed in the range of 2.1 to 3.1, and the Ti-GC-rPMNP group also had a similar cell aspect ratio distribution, indicating that the randomly distributed magnetic nanoparticles had no significant effect on cell morphology. As expected, when anisotropic structures were introduced on the hydrogel coating, the cell aspect ratio was further significantly improved. However, the similar cell aspect ratio distributions of the Ti-GC-aPMNP and Ti-GC-aPMNP+DMF groups indicated that the dynamic mechanical stimulation used in this article had no significant effect on cell morphology.
[0124] Cell orientation degree: The angle θ between the long axis direction and the horizontal line of 10 cells was randomly counted. Figure 4E shows that the angle θ of cells in the isotropic group is distributed in a wide range, which is manifested as a wider box in the box plot; while in the anisotropic group, the cell angle θ is concentrated near the arrangement direction of the hydrogel-coated magnetic particles (Ti-GC-aPMNP: 58.6°, Ti-GC-aPMNP+DMF: 135.8°), indicating that the cells have obvious directional arrangement.
[0125] Example 4 Detection of the effect of the surface modified titanium material prepared in Example 1 on cell osteogenic differentiation
[0126] 1) BMSCs were inoculated on the surface-modified titanium material and cultured for 4 or 7 days, and then washed once with PBS;
[0127] 2) Then, fix with 4% paraformaldehyde for 15 minutes;
[0128] 3) Wash with PBS 3 times, 5 minutes each time;
[0129] 4) The early osteogenic differentiation was determined by ALP kit method, the mid-stage osteogenic differentiation was determined by Sirius red kit method, and the late osteogenic differentiation was determined by Alizarin red kit method.
[0130] Measurement results:
[0131] The results of ALP staining and quantitative detection showed that ( Figure 5 A, 5C), among the three groups of Ti-GC-rPMNP, Ti-GC-aPMNP and Ti-GC-aPMNP+DMF, the ALP positive area in the Ti-GC-aPMNP+DMF group was the largest and the ALP activity was the highest, which was significantly higher than that in the Ti-GC-rPMNP group. Figure 5 B, 5D). The results showed that compared with the Ti-PDA group, the collagen secretion of the Ti-GC group was significantly increased (p<0.05). At the same time, the anisotropic topography and dynamic mechanical stimulation of the hydrogel further increased the collagen secretion of MSCs (p<0.05). Third, the quantitative results of Alizarin red staining at 14 days ( Figure 5 E) shows that the extracellular collagen mineralization level has a consistent trend with ALP activity and collagen secretion.
[0132] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A magnetic hydrogel, characterized in that: It is prepared by the following steps: S1. Preparation of polydopamine-coated magnetic nanocellulose PMNP: S1-1, dissolving carboxylated cellulose nanofibers in deionized water, and ultrasonicating to obtain a cellulose nanofiber solution; S1-2, adding ferrous chloride tetrahydrate and ferric chloride hexahydrate, stirring, adding ammonia water dropwise while stirring, heating and stirring to react, separating with a magnet after the reaction is completed, washing the magnetic product, and obtaining magnetic nanocellulose MNP; S1-3, dispersing MNP in Tris solution, then adding dopamine hydrochloride, mixing by ultrasonication, and shaking on a shaker in the dark to react, after the reaction, washing and freeze-drying the product to obtain PMNP; S2, preparing methacrylylated gelatin GelMA; S3. Preparation of calcium phosphate oligomer CPO: Dissolve CaCl2·2H2O in ethanol, add triethylamine under stirring, and then dropwise add the alcohol solution of H3PO4. After the dropwise addition is completed, centrifuge and wash the solid product to obtain CPO; S4. Preparation of precursor solution for magnetic hydrogel: Under light-proof conditions, GelMA, CPO and photoinitiator were dissolved in PBS solution, and then PMNP was added and mixed evenly to obtain a precursor solution of magnetic hydrogel; S5. Prepare magnetic hydrogel by any of the following methods: a. coating the precursor solution of magnetic hydrogel and curing it with blue-violet light to obtain magnetic hydrogel with randomly distributed magnetic particles; b. After coating, the precursor solution of magnetic hydrogel is subjected to magnetic orientation treatment in a magnetic field, and then cured with blue-violet light to obtain anisotropic magnetic hydrogel.
2. The magnetic hydrogel according to claim 1, characterized in that: Step S1 is specifically as follows: S1-1, dissolving 200 mg of carboxylated cellulose nanofibers in 100 mL of deionized water, and ultrasonicating for 30 minutes to obtain a cellulose nanofiber solution; S1-2, after blowing nitrogen gas into the cellulose nanofiber solution for 20 minutes, 180 mg of ferrous chloride tetrahydrate and 470 mg of ferric chloride hexahydrate were added, and the mixture was stirred for 30 minutes. Ammonia water was added dropwise under stirring to adjust the pH to 10, and the mixture was stirred at 70°C for 30 minutes. 100 mL of deionized water was added to terminate the reaction, and then the mixture was separated by a magnet. The magnetic product was washed with anhydrous ethanol and deionized water in sequence to obtain magnetic nanocellulose MNP; S1-3. Disperse 100 mg of MNPs in 50 mL of Tris solution, then add 50 mg of dopamine hydrochloride, mix by ultrasonication for 5 minutes, shake on a shaker at 50 rpm in the dark overnight, wash the product with deionized water and anhydrous ethanol, and lyophilize to obtain PMNPs.
3. The magnetic hydrogel according to claim 1, characterized in that Step S2 is specifically as follows: At 50°C, 5 g of type A gelatin was added to 50 ml of PBS and stirred until completely dissolved. 6 mL of methacrylic anhydride was added under light-shielded conditions. After reacting for 2 h, 200 mL of PBS preheated to 60°C was added to terminate the reaction. The reaction product was dialyzed in a dialysis bag with a molecular cutoff of 11K Da at 50°C for 4 days. The dialysate in the dialysis bag was taken and freeze-dried to obtain GelMA.
4. The magnetic hydrogel according to claim 1, characterized in that: Step S3 is specifically as follows: 2.94 g of CaCl2·2H2O was dissolved in 0.4 L of ethanol, and 55.45 mL of triethylamine was added under magnetic stirring. Then, an alcohol solution of H3PO4 was added dropwise under magnetic stirring at room temperature. The mixture was reacted for 12 hours, centrifuged, and the solid product was washed to obtain CPO. The alcohol solution of H3PO4 is obtained by dissolving 1.045 mL of H3PO4 in 20.00 mL of ethanol.
5. The magnetic hydrogel according to claim 1, characterized in that: Step S4 is specifically as follows: S4-1. Dissolve GelMA, CPO and photoinitiator LAP in PBS solution at 60°C in the dark, so that the mass volume concentrations of GelMA, CPO and photoinitiator LAP are 15%, 2% and 0.2% respectively; S4-2, adding PMNP and mixing evenly to make the mass volume concentration of PMNP be 0.38-6%, and obtaining a precursor solution of magnetic hydrogel.
6. The magnetic hydrogel according to claim 1, characterized in that: Step S5 is specifically as follows: The magnetic hydrogel is prepared by any of the following methods: a. After coating, the precursor solution of magnetic hydrogel is irradiated with blue-violet light for 30-90 seconds to solidify, thereby obtaining a magnetic hydrogel with randomly distributed magnetic particles; b. After coating, the precursor solution of the magnetic hydrogel is subjected to magnetic orientation treatment in a uniform magnetic field of 60-100 mT for 2-10 seconds and then cured by irradiation with blue-violet light for 30-90 seconds to obtain anisotropic magnetic hydrogel.
7. A surface-modified titanium material having an anisotropic magnetic hydrogel coating, characterized in that: It includes a titanium body and a magnetic hydrogel coating arranged on the surface of the titanium body. The preparation method of the magnetic hydrogel coating is: coating the precursor liquid of the magnetic hydrogel described in any one of claims 1 to 6 on the surface of the titanium body, then performing magnetic orientation treatment in a magnetic field, and curing with blue-violet light to form the magnetic hydrogel coating.
8. The surface-modified titanium material with anisotropic magnetic hydrogel coating according to claim 7, characterized in that: It is prepared by the following method: 1) Polydopamine modification of titanium body: After washing the titanium body, immersing it in an alkaline solution under heating, drying it, and immersing it in a Tris solution, adding dopamine hydrochloride to the Tris solution, reacting on a shaker in the dark, washing and drying the product, and obtaining a polydopamine-modified titanium body; 2) The precursor of the magnetic hydrogel described in any one of claims 1 to 6 is added dropwise to the surface of the polydopamine-modified titanium material body, coated evenly, and then subjected to magnetic orientation treatment in a magnetic field, and blue-violet light curing is used to form the magnetic hydrogel coating, thereby obtaining a surface-modified titanium material having an anisotropic magnetic hydrogel coating.
9. The surface-modified titanium material with anisotropic magnetic hydrogel coating according to claim 8, characterized in that: It is prepared by the following method: 1) Polydopamine modification of titanium body: The titanium body was washed with acetone, anhydrous ethanol and deionized water, then immersed in a 5M NaOH solution at 60°C for 24 hours, dried at 60°C and immersed in a 10mM Tris solution with a pH of 8.5, dopamine hydrochloride was added to the Tris solution to make the concentration of dopamine hydrochloride 1 mg / mL, incubated on a shaker in the dark overnight, the product was washed with deionized water, and dried to obtain a polydopamine-modified titanium body; 2) The precursor of the magnetic hydrogel described in any one of claims 1 to 6 is dropped onto the surface of the polydopamine-modified titanium material body, evenly coated, and then magnetically oriented in a uniform magnetic field of 60-100 mT for 2-10 s, and irradiated with blue-violet light for 30-90 s to solidify the magnetic hydrogel coating to obtain a surface-modified titanium material with an anisotropic magnetic hydrogel coating.
10. An application of a surface-modified titanium material with an anisotropic magnetic hydrogel coating as claimed in any one of claims 7 to 9, which is used as a Ti implant to simulate the physical microenvironment of bone and to construct an in vitro cell culture platform for studying the effects of mechanical stimulation on the adhesion and osteogenic differentiation of BMSCs.
Citation Information
Patent Citations
Structure-controllable magnetic response mineralized collagen coating used for surface of medical metal implant and preparation method thereof
CN107740171A
Preparation method of aminated magnetic nanocrystalline cellulose
CN109517181A
Calcium phosphate oligomer-GelMA hydrogel composite system and preparation method thereof
CN114836047A
Elastomer material based on ionic oligomer crosslinking and preparation method and application thereof
CN118530401A
Cited By
Surface modified titanium stent with magnetic hydrogel coating and preparation method and application of surface modified titanium stent
CN120459367A
Surface with magnetoelectric coupling effect and construction method and application thereof
CN121606740A